METODE PEMBELAJARAN MATEMATIKA PADA ANAK TUNA NETRA DI SEKOLAH DASAR - Lailatul Azkia; Sastra Wijaya; Dhea Amaliya; Nadilah (STKIP Subang, 2024)
Visual ability plays a central role in the learning and guidance process. Visually impaired children often encounter difficulties in achieving minimum learning outcomes due to the limitations of their vision. Mathematics, as an essential subject, is sometimes perceived as challenging and less engaging by elementary school students, including those with special needs. To enhance understanding and academic performance, the teaching methods for mathematics need to be tailored to the students' needs. Specifically, visually impaired children require an approach that leverages their sensory abilities, such as hearing and tactile perception. This study explores three effective mathematics teaching methods for visually impaired children: jarimatika, drill, and blokjes media. The jarimatika method teaches students to use their fingers as counting tools, while the drill method emphasizes repetitive exercises to improve accuracy and speed in arithmetic. Blokjes media are employed to train arithmetic operations, especially downward addition series. Each method has a positive impact on the learning abilities of visually impaired students. Therefore, the selection of suitable mathematics teaching methods and adjustments to the students' conditions are crucial. This research provides insights into the effectiveness of the jarimatika, drill, and blokjes media methods in enhancing the mathematical learning outcomes of visually impaired children. The study utilizes a literature review method based on previous research and underscores the importance of teachers recognizing the specificity of each student and choosing appropriate teaching methods to achieve optimal results.